Degenerative Cervical Myelopathy and the Aging Spine - Nouri, Aria; Tessitore, Enrico; Kotter, Mark R.; Cheng, Joseph (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue contains articles discussing various topics surrounding degenerative cervical myelopathy. The Issue begins with an editorial summarizing the various articles, and is followed by an introductory narrative review focusing on past perspectives, present developments, and future directions. The remaining 11 articles involve a variety of topics, ranging from genetic factors to clinical assessments, imaging, sagittal balance, surgical treatment, and outcome prediction.